What are european union trade preferences worth for sub-saharan african and other developing countries? - (:unkn) unknown (My University, 2009)
This study shows that EU preferences to developing countries were fairlywell utilised in 2001, especially in sub-Saharan Africa. For severalsub-Saharan African countries, the value of EU tariff preferences, evenwithout accounting for tariff rate quota rents, is worth a significantproportion of their world exports. For non-African Least DevelopedCountries, in contrast, we find that the EBA initiative was onlyhalf-utilised approximately, although it is the only preferential regimeavailable to most of them. It is difficult to reach a firm conclusion since2001 was the first year of enforcement of Everything But Arms (EBA), andfigures for 2002 show utilisation is on the rise, but rules of origin appearto limit significantly the value of this scheme. This also likely explainswhy the Generalised System of Preferences (GSP) scheme is significantlyunder-utilised in the manufacturing sector, even when the receiving countryis not eligible to any other preferential regime.
Keywords: African Research